Culture-Based Mathematics Learning Model to Improve Students’ Concept Understanding - Alya Farhana Maulida; Anik Ghufron (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2026)
Elementary school students' understanding of mathematical concepts is still low, one of which is in the material of plane figures. One of the causes is that the learning implemented tends to emphasize memorization. This study aims to create a local culture-based mathematics learning model (PMBBL) to improve students' conceptual understanding. The research subjects were 24 fifth-grade students and 1 teacher. The trial subjects consisted of individual trials, small groups, and field trials involving all 24 fifth-grade students. Data collection methods were through observation, interviews, questionnaires, tests, and expert validation. The research instruments included validation sheets from model experts and material experts, teacher and student practicality questionnaires, and pretest and posttest tests. Data analysis used included qualitative descriptive analysis for observation and interview data, quantitative analysis for feasibility and practicality tests using category score conversion, reliability tests with Cronbach's Alpha, and effectiveness tests using paired sample t-tests via SPSS. The results showed that the PMBBL model met the criteria of being feasible, practical, and effective. The conclusion of this study shows that the integration of local culture in mathematics learning can be an innovative solution in improving the quality of learning in elementary schools. The implications of this research show that the integration of local culture in mathematics learning is able to create contextual, meaningful, and constructive learning, and can be a reference for teachers and other researchers in developing local wisdom-based learning models in different materials and levels.